Multistage textured superhydrophobic polytetrafluoroethylene surface prepared by fabric embossing and thermal annealing - Gu, Dapeng; Song, Kefeng; Chen, Suwen; Liu, Shouyao; Yang, Bingchao; Ma, Xiaoying; Wang, Zibo; Wang, Shuaibing (Materials letters, 2020)
•Multistage PTFE surface was obtained by Fabric embossing and thermal annealing.•Multistage textures include microscale ≈175 µm, ≈10 µm, ≈3 µm and nanoscale ≈380 nm.•Optimum thermal annealing temperatures to superhydrophobicity are 345 and 360 °C. A novel method combined with fabric embossing (embossing with fabric template) and thermal annealing is proposed to prepare multistage textured superhydrophobic polytetrafluoroethylene (PTFE) surface. Multistage (four-stage) textures of microscale Y-grooves (≈175 µm), F-grooves (≈10 µm), warts (≈3 µm), and nanoscale dendrites (≈380 nm) were obtained. The multistage textures endowed the PTFE surface with better superhydrophobicity, comparing with the two-stage textures with Y-grooves and F-grooves or the two-stage textures with warts and dendrites. Optimum superhydrophobicity is obtained at thermal annealing temperatures 345 °C and 360 °C.